Peluang dan Tantangan Penerapan Internet of Things (IoT) dalam Sistem Informasi Manajemen - Meiza Octaria; Muhammad Irwan Padli Nasution (Universitas Katolik Widya Karya Malang, 2024)
For companies across industries, the integration of the Internet of Things (IoT) and management information systems (MIS) offers great potential for digital transformation. This publication explains the benefits and drawbacks of integrating IoT into MIS and how this technology can improve customer experience of products and services, in-depth data analysis, operational efficiency, energy efficiency, and creativity. Implementing IoT in SIM is not without challenges, because there are issues such as data security, interoperability, infrastructure availability, advanced data management, data protection and ethics. With a clear understanding of these pros and cons, companies can take the necessary steps to take full advantage of IoT integration in MIS while maintaining operational security, data protection, and Masu requirements.